A coordinative mechanism of career coaching practice in innovativeness and creativity training programs in higher education – a case study. Issue 3 (4th September 2017) - Chen, Kun-Dang; Huang, Yu-Ye
Abstract : Purpose: The purpose of this study is to explore ways to establish an effective coordinative mechanism to ensure the effective practice of career coaching in innovativeness and creativity training programs in higher education. Design/methodology/approach: This study aims to explore a successful case – that of Wenzhou University College – to elucidate how to establish an effective coordinative mechanism. The Delphi method is an interview approach for obtaining and analyzing case data. Findings: According to research results, first, the causes of conflict were found and an attempt was made to solve these by using a personal system and training program structure revision; the main reasons for the conflicts are an overemphasis on "experts' experience leading" and a "cognitive gap" between experts as coaches and teaching faculties; second, to decrease conflict, a revision of the training program structure will aid the improvement in the specialization for experts and teaching faculties; and third, revision of one's personal system requires the teaching faculties to be from within the industries or companies facilitating the process of these faculties gaining practical experience; moreover, it will be easier if experts are the ones who are communicating how to re-design training programs and cooperative modes. Originality/value: This study provides a coordinative mechanism for the effective practice of innovativeness and creativity training in higher education institutions. On the basis of research results, higher education institutions can effectively develop a training program of innovativeness and creativity based on the concept of career coaching.